2020
DOI: 10.1186/s12913-020-4887-2
|View full text |Cite
|
Sign up to set email alerts
|

Does insurance protect individuals from catastrophic payments for surgical care? An analysis of Ghana’s National Health Insurance Scheme at Korle-Bu teaching Hospital

Abstract: Background: According to the World Health Organization, essential surgery should be recognized as an essential component of universal health coverage. In Ghana, insurance is associated with a reduction in maternal mortality and improved access to essential medications, but whether it eliminates financial barriers to surgery is unknown. This study tested the hypothesis that insurance protects surgical patients against financial catastrophe. Methods: We interviewed patients admitted to the general surgery wards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 38 publications
3
56
2
Order By: Relevance
“… 32 34 Patients insured through the national health insurance scheme who underwent various surgical procedures at the study hospital were reported to be less likely than uninsured patients to face financial catastrophe as a result of their surgery. 35 However, over half of those patients still faced financial catastrophe because of out-of-pocket payments, even with insurance through the national health insurance scheme. 35 Although the national health insurance scheme provided protection against catastrophic health expenditure in our study, only 13/834 (2%) of our insured patients did not make any out-of-pocket payments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 34 Patients insured through the national health insurance scheme who underwent various surgical procedures at the study hospital were reported to be less likely than uninsured patients to face financial catastrophe as a result of their surgery. 35 However, over half of those patients still faced financial catastrophe because of out-of-pocket payments, even with insurance through the national health insurance scheme. 35 Although the national health insurance scheme provided protection against catastrophic health expenditure in our study, only 13/834 (2%) of our insured patients did not make any out-of-pocket payments.…”
Section: Discussionmentioning
confidence: 99%
“… 35 However, over half of those patients still faced financial catastrophe because of out-of-pocket payments, even with insurance through the national health insurance scheme. 35 Although the national health insurance scheme provided protection against catastrophic health expenditure in our study, only 13/834 (2%) of our insured patients did not make any out-of-pocket payments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of financing of health services, there is a National Health Insurance Scheme (NHIS), publicly financed through taxes on goods, services and income, that is theoretically expected cover about 95% of disease conditions [ 12 ]. In reality, however, a significant component critical care is not covered by the NHIS and is usually paid out of pocket [ [12] , [13] , [14] ]. Further details of the Ghanaian Health System are described in the Appendix 2 of the Supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…We recently published a paper evaluating the impact of the national health insurance scheme of Ghana (NHIS) on the risk of financial catastrophe for surgical care at a teaching hospital. We found that despite the benefits of NHIS, more than 60% of insured patients still risk facing financial catastrophe as a result of OOPs for surgical care [ 6 ]. We began to explore the experiences of countries in SSA with national health insurance schemes that include surgical care to develop recommendations for health reform in similar countries in the region.…”
Section: Perspectivesmentioning
confidence: 99%